Public Reception of Dr Tirta Opinion About Vaccination on Instagram: Resepsi Masyarakat Terhadap Opini dr. Tirta Tentang Vaksinasi di Instagram - Fikri Alif Nur Akmaludin; Ainur Rohmaniah (Academia Open, 2024)
This qualitative study investigates the public acceptance of Doctor Tirta's opinions on vaccination, disseminated through his personal Instagram account, amidst a backdrop of increasing social media users, reaching 88 million on Instagram in May 2021. Employing in-depth interviews, the research explores how individuals' experiences, backgrounds, and interests influence their reception of the doctor's vaccination discourse. The results categorize informants into three hegemonic groups: dominant, negotiated, and opposition. This study contributes valuable insights into the nuanced dynamics shaping public perceptions of vaccine-related information on social media, with potential implications for public health communication strategies. Highlights : Social Media Dynamics: This study delves into the intricacies of public reception of vaccination-related content on Instagram, acknowledging the platform's role in shaping opinions. Individual Factors: Examining how personal experiences, backgrounds, and interests influence the way individuals interpret and accept information about vaccinations shared by Doctor Tirta on his personal Instagram. Hegemonic Categories: The research categorizes informants into dominant, negotiated, and opposition groups, providing a nuanced understanding of the diverse public responses to vaccination discourse on social media. Keywords: Instagram, Vaccination, Public Perception, Social Media Influence, Qualitative Study